Analytical Insights on the Position, Challenges, and Potential for Promoting OER in ODeL Institutions in Africa - Muganda, Cornelia K.; Samzugi, Athuman S.; Mallinson, Brenda Justine (International Review of Research in Open and Distributed Learning, 2016)
This paper shares analytical insights on the position, challenges and potential for promoting Open Educational Resources (OER) in African Open Distance and eLearning (ODeL) institutions. The researchers sought to use a participatory research approach as described by Krishnaswamy (2004), in convening a sequence of two workshops at the Open University of Tanzania (OUT) as a strategy for collecting data to obtain the aforementioned insight. The principal workshop objectives were to analyse the existing status of OER at the OUT and subsequently to share lessons learned in OER creation and production, integration and use, and hosting and dissemination. Other objectives were to discuss the rationale for an institutional OER policy and identify a suitable work-flow process for developing OER at the OUT. The workshop participants were purposively selected for their experience in co-developing OER materials with various outside organisations. The study included 28 representatives of the OUT academic units, and one facilitator from OER Africa. Research techniques used to collect data included a questionnaire, focused group discussions, presentations, and panel discussions. Results indicated that OUT staff were willing to engage with OER but had limited awareness, skills and competencies in the creation, integration and use of OER. The outcome of the study was the development of nine draft OER resolutions expressing needs that include the development of a comprehensive institutional OER policy related to existing institutional policies in order to guide, support and promote research and sustainable OER practice via holistic participation. Enabling strategies included capacity building, increased internal and external collaboration, and enhanced access to and visibility of OER via the institutional repository.